Revisiting an Expression Dataset of Discordant Inflammatory Bowel Disease Twin Pairs Using a Mutation Burden Test Reveals CYP2C18 as a Novel Marker - Du, Juan; Yin, Jie; Du, Haojie; Zhang, Jiawei (Frontiers in Genetics, 2021)
The aim of this study was to investigate the expression features of discordant inflammatory bowel disease (IBD) twin pairs to identify novel molecular features and markers. We collected an expression dataset of discordant twin pairs with ulcerative colitis and performed integrative analysis to identify the genetic-independent expression features. Through deconvolution of the immune cell populations and tissue expression specificity, we refined the candidate genes for susceptibility to ulcerative colitis. We found that dysregulated immune systems and NOD-related pathways were enriched in the expression network of the discordant IBD twin pairs. Among the identified factors were significantly increased proportions of immune cells, including megakaryocytes, neutrophils, natural killer T cells, and lymphatic endothelial cells. The differentially expressed genes were significantly enriched in a gene set associated with cortical and medullary thymocytes. Finally, by combining these expression features with genetic resources, we identified some candidate genes with potential to serve as novel markers of ulcerative colitis, such as CYP2C18. Ulcerative colitis is a subtype of inflammatory bowel disease and a polygenic disorder. Through integrative analysis, we identified some genes, such as CYP2C18, that are involved in the pathogenesis of IBD as well as some candidate therapeutic targets, such as LOXL2.